Implementation of Global Supply Chains as a Strategy for Increasing National Competitiveness - Syromyatnikov, Denis; Konev, Pavel; Popov, Mikhail; Sultanova, Naila (ExcelingTech, 2020)
Abstract— Today competitiveness depends not only on price but also on customer service and delivery time. The creation of an effective infrastructure and the development of global supply chains is the key condition for increasing competitiveness. The study is based on the analysis of peer-reviewed literature, as well as the information publicly available on official websites. The purpose of the research is to conduct a thorough analysis and compare the level of competitiveness and efficiency throughout the supply chain of logistics services in different countries. The logistics efficiency and global competitiveness indicators have been analyzed. It has been concluded that favorable conditions in the country evidenced by its high ranking in the International Logistics Performance Index determine the potential for the implementation of global chains and provide opportunities for increasing competitiveness.